2020
DOI: 10.1186/s12891-020-03495-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness in older women with osteoporosis and vertebral fracture after a resistance and balance exercise programme: 3-month post-intervention follow-up of a randomised controlled trial

Abstract: Background Exercise is recommended for individuals with vertebral fractures, but few studies have investigated the effect of exercise on outcomes of importance for this population. Post-intervention effects of exercise are even less studied. The objective of this study was to evaluate habitual walking speed and other health-related outcomes after cessation of a 3-month exercise intervention. Methods This follow-up study was conducted 3 months post-intervention of a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
1
19
0
2
Order By: Relevance
“…Moreover, it should be noted how calcium, vitamin D, and amino acids supplementation should be considered in a multidisciplinary integrated intervention combined with lifestyle education to prevent or to counteract the developing of osteosarcopenia [ 3 , 49 , 50 , 51 , 52 ]. Almost 70% of the PRM physicians involved prescribed therapeutic exercise in their clinical practice; these findings are in line with the available literature suggesting its beneficial effects of exercise in terms of pain, posture, physical performance, and HRQoL [ 53 , 54 , 55 , 56 , 57 ]. In this scenario, a recent Cochrane Systematic Review performed by Gibbs et al [ 58 ] supported exercise therapy as an effective intervention in functional outcomes improvement in patients suffering from osteoporotic vertebral fractures with moderate evidence.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, it should be noted how calcium, vitamin D, and amino acids supplementation should be considered in a multidisciplinary integrated intervention combined with lifestyle education to prevent or to counteract the developing of osteosarcopenia [ 3 , 49 , 50 , 51 , 52 ]. Almost 70% of the PRM physicians involved prescribed therapeutic exercise in their clinical practice; these findings are in line with the available literature suggesting its beneficial effects of exercise in terms of pain, posture, physical performance, and HRQoL [ 53 , 54 , 55 , 56 , 57 ]. In this scenario, a recent Cochrane Systematic Review performed by Gibbs et al [ 58 ] supported exercise therapy as an effective intervention in functional outcomes improvement in patients suffering from osteoporotic vertebral fractures with moderate evidence.…”
Section: Discussionsupporting
confidence: 71%
“…The improved muscle strength among the participants in the interventions groups is gripping, considering that muscle strength naturally may decline with age. Maintenance of muscle strength may prevent loss of functional dependence [ 33 ]. A systematic review reported that exercise might prevent falls and fall-related fractures and reduce risk factors for falls in individuals with low bone mineral density [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of muscle strength may prevent loss of functional dependence [ 33 ]. A systematic review reported that exercise might prevent falls and fall-related fractures and reduce risk factors for falls in individuals with low bone mineral density [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the training period ended, walking speed was not significantly different between the intervention group and the control group (mean difference 0.04 m/s). Walking speed was measured again in both groups after 3 months and there was also no statistically significant difference (0.03 m/s) [66,67]. The research by Diem S. J. et al concluded that women with slow walking speed were less likely to be independent than women with good walking speed [68].…”
Section: Impact Of Training In Elderly Age On Bones and Healthmentioning
confidence: 93%
“…The research by Diem S. J. et al concluded that women with slow walking speed were less likely to be independent than women with good walking speed [68]. Nevertheless, a significant improvement in balance and reduction in fear of falling was observed for the intervention group in both measurements [66,67]. Additionally, a study by Otero M. et al also confirmed the positive effect of a physical exercise program based on balance and strength exercises on improving balance but also strength in women with osteoporosis [69].…”
Section: Impact Of Training In Elderly Age On Bones and Healthmentioning
confidence: 98%